Caspase-7 participates in differentiation of cells forming dental hard tissues - Matalova, Eva; Lesot, Herve; Svandova, Eva; Vanden Berghe, Tom; Sharpe, Paul T; Healy, Christopher; Vandenabeele, Peter; Tucker, Abigail S (Development, growth & differentiation, 2013)
Apoptosis during tooth development appears dependent on the apoptotic executioner caspase-3, but not caspase-7. Instead, activated caspase-7 has been found in differentiated odontoblasts and ameloblasts, where it does not correlate with apoptosis. To further investigate these findings, the mouse incisor was used as a model. Analysis of caspase-7-deficient mice revealed a significant thinner layer of hard tissue in the adult incisor. Micro computed tomography scan confirmed this decrease in mineralized tissues. These data strongly suggest that caspase-7 might be directly involved in functional cell differentiation and regulation of the mineralization of dental matrices.
Keywords: Odontoblasts; Mice, Knockout; Incisor; Cell Proliferation; Odontogenesis; buněčná diferenciace; Caspase 7; imunohistochemie; ameloblasty; zubní sklovina; řezáky; myši knockoutované; Time Factors; rentgenová mikrotomografie; Dental Enamel; Ameloblasts; Animals; kaspasa 7; Immunohistochemistry; odontogeneze; zvířata; časové faktory; myši inbrední C57BL; X-Ray Microtomography; myši; proliferace buněk; Mice, Inbred C57BL; Mice; odontoblasty; Cell Differentiation